Clinical characteristic, treatment, and mortality among cancer and non-cancer patients presented with incidental pulmonary embolism - Chai-Adisaksopha, Chatree; Chaiwong, Warawut; Niprapan, Piangrawee; Tantiworawit, Adisak; Bumroongkit, Chaiwat (Frontiers in Medicine, 2025)
IntroductionCancer patients are at an increased risk of developing venous thrombosis Advances in multidetector computed tomography (CT) scanners have facilitated the detection of pulmonary embolism (PE). However, the natural course of incidental PE (IPE), particularly in cancer patients, remains controversial.MethodsThis retrospective cohort study was conducted at a tertiary medical center in Thailand. Patients aged 15 years or older who were diagnosed with PE between 2011 and 2020 were included. The study population was divided into two groups: the IPE group and the suspected PE (SPE) group. The primary outcome was 30-day mortality.ResultsA total of 736 patients with acute PE were included in the analysis, with 281 classified as having IPE and 455 as having SPE. Active cancer was more prevalent in the IPE group compared to the SPE group (70.8% vs. 46.6%, p < 0.001). IPE presented with fewer PE-related symptoms and lower markers of severity, and received LMWH more often but with longer time to first anticoagulant (median 24 h vs. 2.78 h; p < 0.001). Thirty-day mortality was observed in 25.72% of the IPE group and 30.24% of the SPE group (p = 0.064). Subgroup analysis of cancer patients showed that those with IPE had a lower mortality rate (24.12%) compared to those with SPE (44.34%, p < 0.001). However, in adjusted Cox models, IPE was not independently associated with 30-day mortality (HR 1.42, 95% CI 0.84–2.43, p = 0.194).ConclusionIPE is common in cancer and is associated with delayed anticoagulation but similar adjusted short-term mortality to SPE. System-level pathways to expedite treatment for IPE may improve care, especially in cancer patients.